Effect of black soldier fly larvae protein on the texture of meat analogues. (1st May 2023) - Miron, Lucian; Montevecchi, Giuseppe; Macavei, Laura Ioana; Maistrello, Lara; Antonelli, Andrea; Thomas, Menno
Abstract: Black soldier fly larvae are considered an alternative source of protein due to their high protein content and low environmental impact of farming. The effect of incorporation of black soldier fly larvae protein (87.6 ± 2.4 g/100 g content) on meat analogues textural characteristics was determined and compared with those of meat analogues prepared with other alternative sources of protein such as soy protein isolate and vital wheat gluten, while beef round, chicken breast, and a commercial plant-based meat analogue were used as reference matrices. Textural characteristics of the experimental meat analogues were used as response variables in robust regression models (R 2  > 0.96) built to determine the main effects and interactions of proteins. Black soldier fly larvae protein decreased the textural characteristics of meat analogues as its amount in the formulation increased. The interaction of black soldier fly larvae protein with soy protein affected the hardness and chewiness of meat analogues, whereas the interaction with wheat gluten only affected their cohesiveness. Black soldier fly larvae protein can partially replace traditional proteins in meat analogues. The optimal incorporations of black soldier fly larvae protein in meat analogues which mimics textural characteristics of chicken breast and plant-based meat analogues were 6.7 g/100 g and 21.5 g/100 g, respectively. Highlights: Incorporation of black soldier fly protein in meat analogues; Protein content in black soldier fly larvae was 87.6 g/100 g; Texture characteristics of meat analogues were assessed by regression models; Best formulations contained 6.7 g/100 g and 21.5 g/100 g insect protein.